PENGARUH TINGKAT KEMISKINAN DAN PENGELUARAN PEMERINTAH BIDANG PENDIDIKAN TERHADAP INDEKS PEMBANGUNAN MANUSIA - Invantoro, Deni; Efriyenti, Dian (SCIENTIA JOURNAL, 2019)
Human DevelopmenttIndex (HDI) is an important thing to assess the success of funds that allocated for human development. And than, this study aims to analyzetthe influenceiof poverty levels and governmentiexpenditure on education on the human development index. The analysisitechnique usedlis multipleilineariregression. Theitype of data used is time series data, with populations sourced from the Batam City Central Bureau of Statistics and the Regional Financial and Asset Management Agency of Batam City. The sample used in this studyiis the Panel data for 2010-2017. Based on the resultsoof testing the hypothesis, itiwasifound that the poverty level had a positive effect onethe human development indexiin theicityiof Batam. Whileegovernment spending oneeducation has a positive and significant effect on the human developmen iindex in the city of Batam. The determination coefficient value is 0.952 which indicates that the influence of poverty levels and government expenditure on education on the human developmenttindex in Batam city is 95.2%iandithe remainingi4.8% is influencediby other variablesioutside of this study.t